Framing Colonial Australia: A Socio-historical Articulation of the Display of Art - Anita Gowers (Sillages Critiques)
During the first half of the nineteenth century European settlement was consolidated in Australia. The industrialisation of convict transportation saw vast numbers of lawbreakers sent unceremoniously to Australian shores, with the newly emergent convict settlements of Hobart Town and Sydney quickly becoming Antipodean slums: untidy, unruly and in dire need of civilising. In this context, the cultivation of the arts was seen as a means of rehabilitation, moving the nomenclature away from “penal colony” to the more desirable descriptor “free society”. Amongst the early arrivals was a small but remarkable group of talented and knowledgeable artists, the most famous of whom was John Glover. These artists disembarked with their trade skills and traditions that included established conventions regarding the display of paintings. In the Western European art ecosystem of the early nineteenth century, it was de rigueur to present oil on canvas works in ornate gilt frames, as without a suitable frame an artwork would not be displayed, sold or exhibited. Arriving with limited access to complementary art services and resources on the other side of the world to the centres of taste and civilisation, how did these artists frame their works? Who were the frame makers and what materials were available? Remarkably, Australian art historians have published little on frames of Australian colonial artists and more specifically the framing intentions of the artists themselves. This paper takes a socio-historiographical perspective, drawing on primary source materials including diaries, manuscripts, publications and original frames, to discuss the frames of a select number of formative Australian artists. It also explores the interconnections between the artist, the work and the frame. Understanding the materials to hand, the framing conventions of the day and the ways these early colonial artists wanted their work displayed provides vital evidence for curators and conservators informing the period framing decisions of contemporary institutions.